Whatever happened to party government? : controversies in American political science - Wickham-Jones, Mark, 1962- (University of Michigan Press, 2018)
"In 1950, the Committee on Political Parties of the American Political Science Association (APSA) published its much-anticipated report, Toward a More Responsible Two-Party System. Highly critical of the existing state of affairs, the report became extremely controversial: before publication, scholars attacked the committee's draft and suggested it should be suppressed. When released it received a barrage of criticisms. Most academics concluded it was an ill-conceived and mistaken initiative. Mark Wickham-Jones provides the first full, archival-based assessment of the arguments within APSA about political parties and the 1950 report. He details the report's failure to generate wider discussion between media, politicians, and the White House. He examines whether it was dominated by a dogmatic attachment to "party government," and charts the relationship between behavioralists and institutionalists. He also discusses the political dimension to research during the McCarthyite years, and reflects on the nature of American political science in the years after 1945, the period in which behavioralism (which privileges the influence of individuals over institutions) became dominant. Detailing APSA's most direct and significant intervention in the political process, Wickham-Jones makes an important contribution to debates that remain in the forefront of discussions about American politics"--